Blur Detection Sensitivity Increases in Children Using Orthokeratology - Xu, Jingjing; Tao, Chunwen; Mao, Xinjie; Lu, Xin; Bao, Jinhua; Drobe, Björn; Chen, Hao (Frontiers in Neuroscience, 2021)
Purpose To investigate changes in blur detection sensitivity in children using orthokeratology (Ortho-K) and explore the relationships between blur detection thresholds (BDTs) and aberrations and accommodative function. Methods Thirty-two children aged 8–14 years old who underwent Ortho-K treatment participated in and completed this study. Their BDTs, aberrations, and accommodative responses (ARs) were measured before and after a month of Ortho-K treatment. A two forced-choice double-staircase procedure with varying extents of blur in three images (Tumbling Es, Lena, and Street View) was used to measure the BDTs. The participants were required to judge whether the images looked blurry. The BDT of each of the images (BDT_Es, BDT_Lena, and BDT_Street) was the average value of the last three reversals. The accommodative lag was quantified by the difference between the AR and the accommodative demand (AD). Changes in the BDTs, aberrations, and accommodative lags and their relationships were analyzed. Results After a month of wearing Ortho-K lenses, the children’s BDT_Es and BDT_Lena values decreased, the aberrations increased significantly (for all, P ≤0.050), and the accommodative lag decreased to a certain extent [T(31) = 2.029, P = 0.051]. Before Ortho-K treatment, higher-order aberrations (HOAs) were related to BDT_Lena (r = 0.463, P = 0.008) and the accommodative lag was related to BDT_Es (r = −0.356, P = −0.046). After one month, no significant correlations were found between the BDTs and aberrations or accommodative lags, as well as between the variations of them (for all, P ≥ 0.069). Conclusion Ortho-K treatment increased the children’s level of blur detection sensitivity, which may have contributed to their good visual acuity.